Capital Inflows, Financial Structure and Housing Booms. Issue 2 (1st April 2014) - Sá, Filipa; Towbin, Pascal; Wieladek, Tomasz
Abstract: We use a panel VAR to study the effect of shocks to capital inflows, which are identified using sign restrictions, on the housing market in OECD countries. To explore how effects of these shocks change with the structure of the mortgage market and the degree of mortgage securitization, we allow the VAR coefficients to vary with mortgage-market characteristics. Our results indicate that capital-inflow shocks have a significant and positive effect on real house prices, real credit available to the private sector, and real residential investment. The responses of these variables are stronger in countries with more developed mortgage markets and in countries where securitization is allowed.